A review and case study of Rhododendron moulmainense highlights the feasibility and adaptation of evergreen Rhododedron plants to current environmental challenges - Liu, Sijia; Zhuang, Peng; Cai, Zipeng; Bai, Yuqing; Peng, Jingen; Khan, Zaid; Zhang, Luwen; Li, Rongsheng; Yang, Jinchang; Cai, Hongyue; Xie, Lijuan (Frontiers in Plant Science, 2025)
Alpine rhododendrons have high ecological, ornamental, and recreational value due to its colourful flowers and tall trees, and making it a promising candidate for urban gardens. However, its long growth cycle and lack of adaptation to low altitude environments often result in leaf burning and weak plant growth, hindering its widespread use in urban gardens. Moreover, the existing literature often fails to present key information on propagation techniques and low altitude acclimatisation of alpine rhododendrons in a clear and concise manner. To tackle this issue, we used the example of the alpine evergreen azalea, Rhododendron moulmainense, which grows in the southernmost part of the latitude. We conducted a comprehensive review of research advances in the evolutionary status of rhododendrons, mycorrhizal symbiosis, flower bud differentiation, environmental adaptation, and reproduction. By integrating various aspects, this review offers valuable insights into the domestication of alpine rhododendron at low altitudes and proposes solutions to address their environmental adaptation, with the aim of promoting their use in urban gardens and fully utilising their role in ecological stabilisation.